PS-051 Risks related to drug recalls: a case report. (24th February 2014) - Malriq, A; Sapin, A; Derain, L; Locher, F; Meunier, A
Abstract : Background: In case of anomalies or incidents concerning batches of medicine, the ANSM (French Agency for the Safety of Health Products) proceeds to the recall of the affected batches. The recalls are needed for various reasons: packaging errors, defects affecting the quality of the product, statutory reasons, etc. Hospitals are then obliged to implement the recall but it can sometimes lead to drug shortages when only the batch (es) concerned is (are) held. Purpose: To describe risks related to drug recalls when all the batches held in stock are recalled and when the drug quality is not affected. This paper focuses on the recall of one batch of an injectable local anaesthetic due to the presence of a leaflet that gave the wrong indications. Materials and methods: A risk analysis was carried out: the risks of implementing the recall were compared to the risks of continuing to use this medicine. Results: Other dosages of this anaesthetic were available (2–7.5-10 mg/mL vials) but the substitution could cause dosage errors in operating theatres, so serious consequences for patients could occur. The main risk of using this recalled anaesthetic was prescription errors. As our hospital practitioners use a medical prescription writing software including a medical database, they do not consult the drug leaflet to prescribe. However, nurses generally use the leaflet as an aid for administering this intravenous drug. All information written on the leaflet, except the indications, was valid so the probability of nurses making mistakes was very low. For those two reasons, serious consequences for patients were very unlikely to happen. So, we decided, in agreement with the Committee of Medicines and Sterile Medical devices, not to remove the batch concerned in our hospital. The erroneous leaflets were removed from packs and an information note including a new leaflet was sent to users. Conclusions: This example illustrates some of the difficulties and risks related to drug recalls. As sometimes drug recalls can lead to consequences for patients, a risk analysis must be carried out and a multidisciplinary decision is needed. Since this event, a risk analysis has been included in our internal drug recall management procedure. However, if an incident happens in our hospital with a recalled medicine, the pharmacist is legally responsible. No conflict of interest.